Urban planning in the digital age : from smart city to open government? - Douay, Nicolas (Intellectual technologies set, 2018)
Technological changes have often produced important social changes that translate into spatial and planning practice. Whereas the intelligent city is one of the unavoidable and even dominant concepts, digital uses can influence urban planning in four different directions. These scenarios are represented by a compass composed of a horizontal axis opposing institutional and non-institutional actors, and a second axis with open and closed opposition.